2007
DOI: 10.1590/s1415-47572007000100019
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and antigenotoxic effects of Fucus vesiculosus extract on cultured human lymphocytes using the chromosome aberration and Comet assays

Abstract: The brown seaweed Fucus vesiculosus (Fucales, Fucaceae) was screened for its protective activity using doxorubicin-induced DNA damage in human lymphocytes. In this study, we assessed the genotoxic and antigenotoxic potential of three different concentrations (0.25, 0.5 and 1.0 mg mL -1 ) of F. vesiculosus aqueous extract using the chromosome aberration and Comet assays. Treatment of human lymphocyte cultures with 0.25, 0.5 and 1.0 mg mL -1 F. vesiculosus aqueous extract had no effect on the chromosome aberrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The existence of SA’s various antioxidant scavengers, such as fucoidans, may explain its protective activity against Cr-induced genotoxicity [ 67 ]. The antigenotoxicity of fucoidan was previously identified against doxorubicin-induced DNA damage and proved in terms of chromosome aberrations and comet in human lymphocytes [ 68 ]. Accordingly, other study reported that fucoidan protects mice from 4-NQO-induced genetic damage in terms of LPO, 8-OHdG, micronuclei, comet and apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of SA’s various antioxidant scavengers, such as fucoidans, may explain its protective activity against Cr-induced genotoxicity [ 67 ]. The antigenotoxicity of fucoidan was previously identified against doxorubicin-induced DNA damage and proved in terms of chromosome aberrations and comet in human lymphocytes [ 68 ]. Accordingly, other study reported that fucoidan protects mice from 4-NQO-induced genetic damage in terms of LPO, 8-OHdG, micronuclei, comet and apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of human lymphocyte cultures with ADR induced chromosome aberrations and DNA damage. 29 Khan et al 30 reported that ADR and idarubicin caused chromosomal aberration and micronucleus in cultured human lymphocytes. Dimanche-Boitrel et al 31 mentioned that most of the anticancer therapies induce tumor cell death through the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of DNA damage can be represented using parameters like tail moment, olive moment, and percentage of DNA in tail. The brown seaweed Fucus vesiculosus was evaluated for genotoxic activity by Leite-Silva et al [ 34 ] and the results suggest that the seaweed did not exhibit genotoxic effect in cultured human lymphocytes. Similarly the non-genotoxic property of G. acerosa and S. wightii was evaluated and the results show that the extracts did not induce DNA damage, which was verified by the decrease in the parameters like tail moment, olive moment, and percentage of DNA in tail.…”
Section: Discussionmentioning
confidence: 99%